Effects of Hydrogen Sulfide on a Rat Model of Sepsis-associated Encephalopathy - 陈娣 潘昊 李醇文 兰秀彩 刘蓓蓓 杨光田 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
To investigate the interaction and involvement of sodium hydrosulfide （NaHS）, a H2S donor, on hippocampus of rats suffering from sepsis-associated encephalopathy, rats were subjected to cecal ligation and puncture （CLP）-induced sepsis. Adult male Sprague-Dawley rats were randomly divided into four groups： Sham group, CLP group, CLP＋NaHS group and CLP＋aminooxyacetic acid （AOAA, an inhibitor of H2S formation） group. The four groups were observed at 3, 6, 9, 12 h after treatment. We examined hippocampal H2S synthesis and the expression of cystathionine-β-synthetase （CBS）, a major enzyme involved in the H2S synthesis in hippocampus. CBS expression was detected by reverse transcription polymerase chain reaction （RT-PCR）. The concentrations of inflammatory cytokines （TNF-α, IL-1β） were determined in hippocampus by using enzyme-linked immunosorbent assay （ELISA）. Neuronal damage was studied by histological examination of hippocampus. In CLP group, H2S synthesis was significantly increased in hippocampus compared with sham group and it peaked 3 h after CLP （P〈0.05）. Sepsis also resulted in a significantly upregulated CBS mRNA in hippocampus. The levels of TNF-α and IL-1β in the hippocampus were substantially elevated at each time point of measurement （P〈0.05）, and they also reached a peak value at about 3 h. Administration of NaHS significantly aggravated sepsis-associated hippocampus inflammation, as evidenced by TNF-α and IL-1β activity and histological changes in hippocampus. In septic rats pretreated with AOAA, sepsis-associated hippocampus inflammation was reduced. It is concluded that the rats subjected to sepsis may suffer from brain injury and elevated pro-inflammatory cytokines are responsible for the process. Furthermore, administration of H2S can increase injurious effects and treatment with AOAA can protect the brain from injury.